Increased Excitatory Synaptic Transmission of Dentate Granule Neurons in Mice Lacking PSD-95-Interacting Adhesion Molecule Neph2/Kirrel3 during the Early Postnatal Period - Roh, Junyeop D.; Choi, Su-Yeon; Cho, Yi Sul; Choi, Tae-Yong; Park, Jong-Sil; Cutforth, Tyler; Chung, Woosuk; Park, Hanwool; Lee, Dongsoo; Kim, Myeong-Heui; Lee, Yeunkum; Mo, Seojung; et al. (Frontiers in Molecular Neuroscience, 2017)
Copy number variants and point mutations of NEPH2 (also called KIRREL3) gene encoding an immunoglobulin superfamily adhesion molecule have been linked to autism spectrum disorders, intellectual disability and neurocognitive delay associated with Jacobsen syndrome, but the physiological roles of Neph2 in the mammalian brain remain largely unknown. Neph2 is highly expressed in the dentate granule (DG) neurons of the hippocampus and is localized in both dendrites and axons. It was recently shown that Neph2 is required for the formation of mossy fiber filopodia, the axon terminal structure of DG neurons forming synapses with GABAergic neurons of CA3. In contrast, however, it is unknown whether Neph2 also has any roles in the postsynaptic compartments of DG neurons. We here report that, through its C-terminal PDZ domain-binding motif, Neph2 directly interacts with PSD-95, an abundant excitatory postsynaptic scaffolding protein. Moreover, Neph2 protein is detected in the brain postsynaptic density fraction and interacts with PSD-95 in synaptosomal lysates. Functionally, loss of Neph2 in mice leads to age-specific defects in the synaptic connectivity of DG neurons. Specifically, Neph2–/– mice show significantly increased spontaneous excitatory synaptic events in DG neurons at postnatal week 2 when the endogenous Neph2 protein expression peaks, but show normal excitatory synaptic transmission at postnatal week 3. The evoked excitatory synaptic transmission and synaptic plasticity of medial perforant pathway-DG synapses are also normal in Neph2–/– mice at postnatal week 3, further confirming the age-specific synaptic defects. Together, our results provide some evidence for the postsynaptic function of Neph2 in DG neurons during the early postnatal period, which might be implicated in neurodevelopmental and cognitive disorders caused by NEPH2 mutations.